2021
DOI: 10.1097/01.ogx.0000767216.18371.e9
|View full text |Cite
|
Sign up to set email alerts
|

Chimeric Contribution of Human Extended Pluripotent Stem Cells to Monkey Embryos Ex Vivo

Abstract: 8.6-11) for septum resection and 9.2 months (95% CI, 7.8-11) for expectant management (log rank P = 0.64) (hazards ratio, 0.83; 95% CI, 0.39-1.9). The per-protocol analysis likewise showed no evidence of a difference in reproductive outcomes between the 2 groups.The results of this study find that septum resection did not improve live birth rate compared with expectant management among women with a septate uterus desiring pregnancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…In general, the capacity to produce interspecies chimeras with somatic and germline contribution is expected to be dependent on species similarity and a physiologically receptive environment that is permissive for two distinct genotypes to coalesce in the same organism, as demonstrated in recent years for adult or fetal mouse-rat, human-monkey, and human-pig chimeras (Das et al, 2020;Maeng et al, 2021;Tan et al, 2021;Zheng et al, 2021a). Furthermore, contribution to interspecies chimerism is highly dependent on cell competition and the capacity of PSCs to overcome evolutionary barriers (Ballard and Wu, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…In general, the capacity to produce interspecies chimeras with somatic and germline contribution is expected to be dependent on species similarity and a physiologically receptive environment that is permissive for two distinct genotypes to coalesce in the same organism, as demonstrated in recent years for adult or fetal mouse-rat, human-monkey, and human-pig chimeras (Das et al, 2020;Maeng et al, 2021;Tan et al, 2021;Zheng et al, 2021a). Furthermore, contribution to interspecies chimerism is highly dependent on cell competition and the capacity of PSCs to overcome evolutionary barriers (Ballard and Wu, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…One pioneering study injected human PSCs into pig blastocysts, but found limited contribution to chimeras (Wu et al, 2017); this may be due to the poor quality of human (primate) iPSCs or simply because of the large evolutionary distance between humans and pigs that are estimated to have diverged $91 million years ago (Jørgensen et al, 2005). In addition, due to ethical concerns, the injection of human iPSCs into primate embryos is limited to in vitro experiments only (Tan et al, 2021). Moreover, while under certain circumstances it is ethical to transplant human PSCs into rodent and pig blastocysts (Wu et al, 2016;Suchy and Nakauchi, 2017), it is currently ethically impermissible to inject them into NHP embryos and transplant the chimeric embryos into a female NHP recipient (Suchy and Nakauchi, 2017;Hermere ´n, 2015;Tan et al, 2021), and therefore we did not inject human iPSCs into the rhesus blastocysts.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, due to ethical concerns, the injection of human iPSCs into primate embryos is limited to in vitro experiments only (Tan et al, 2021). Moreover, while under certain circumstances it is ethical to transplant human PSCs into rodent and pig blastocysts (Wu et al, 2016;Suchy and Nakauchi, 2017), it is currently ethically impermissible to inject them into NHP embryos and transplant the chimeric embryos into a female NHP recipient (Suchy and Nakauchi, 2017;Hermere ´n, 2015;Tan et al, 2021), and therefore we did not inject human iPSCs into the rhesus blastocysts. Instead, we injected optimized iPSCs from chimpanzees (which are the closest living ancestors to humans; King and Wilson, 1975) into rhesus macaque blastocysts.…”
Section: Discussionmentioning
confidence: 99%
“…Blastoids from naïve pluripotent stem cells model pre-implantation and post-implantation human embryos (Aguilera-Castrejon et al, 2021; Kagawa et al, 2022; Li et al, 2019; Rivron et al, 2018; Tarazi et al, 2022; Vrij et al, 2022; Yu et al, 2021). The recently established expanded potential stem cells (EPSCs) possess the capacity to derive both embryonic and extraembryonic tissues (Gao et al, 2019; Tan et al, 2021; Yang et al, 2017). The use of EPSCs possesses advantages in modeling cell-cell interactions in human embryonic development, especially to examine extraembryonic tissues regulating the differentiation of embryonic tissues.…”
Section: Introductionmentioning
confidence: 99%